Approach to resolving pollution of river water associated with human activities in Tanzania - Bomani Saida Sumari (African Journal of Environmental Economics and Management, 2018)
Lack of coordination among sectors and institutions is among factors that results in ineffective management of natural resources in most basins in east Africa including Tanzania. In many cases, this has reported to be the most factor contributing natural resources degradation and conflicts between societies. This paper presents findings on different factors affecting the sustainability of the Mara River Basin (MRB) and proposes a management framework that will bring about sustainable resources use in the basin. The study was limited to the MRB part of Tanzania and multiple approaches were used in data collection. The MRB is experiencing a number of management problems including deforestation, land degradation and pollution of the river water associated with human activities. Institutional framework for natural resource management (NRM) is rather sectoral thus lacking integration and sometimes results into conflicting efforts to conserve natural resources. It is evident that some cultural attitudes including gender have positive impact on natural resources management such as the customary land tenure system. For sustainability of the MRB resources, a well coordination of natural resources and livelihoods projects, programs and stakeholders’ participation is a key factor without neglecting cultural aspects. Furthermore, different policies need to be considered by linking them together to achieve sustainability.